Etos Kerja dan Budaya Kerja Perempuan Melayu di Era Globalisasi: Etos Kerja dan Budaya Kerja Perempuan Melayu di Era Globalisasi - Lemiyana; Ris'an Rusli; Maftukhatusolikhah; Fira Puspita (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2024)
This research aims to examine the work ethic and work culture as well as the factors that influence the work ethic and work culture of Malay women in the Era of Globalization. The research focus is on Women Traders at the Pasar Induk Jakabaring. This type of research is qualitative research with a descriptive approach which aims to describe various facts accurately and systematically. There are two sources of data in this research, namely primary sources such as female traders. Secondary data sources through literature searches from books and journals. The research respondents were 8 traders. Data collection techniques through in-depth interviews, direct observation at the Pasar Induk Jakabaring Palembang and documentation. The collected data was analyzed using an interactive model, namely data reduction, data presentation and drawing conclusions. The results of the research show that Palembang Malay women as traders at the Pasar Induk Jakabaring have a very good work ethic and a high work culture, namely the spirit of hard work, responsibility for family and work, having a spirit of mutual cooperation, respecting time, having a foresight and sincerity in work. Malay female traders also have an important role in meeting family needs, especially in economic matters.